2006
DOI: 10.1002/cjoc.200690118
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐assisted Cinnamaldehyde Hydrogenation to Cinnamyl Alcohol at Atmospheric Pressure over Ru‐B Amorphous Catalyst

Abstract: The ultrafine Ru-B amorphous alloy catalyst was prepared by chemical reduction with KBH 4 . During liquid phase hydrogenation of cinnamaldehyde at atmospheric pressure, the Ru-B catalyst prepared exhibited excellent selectivity to cinnamyl alcohol. When the hydrogenation was performed with ultrasonic irradiation, the reaction rate could be greatly enhanced while the selectivity to cinnamyl alcohol remained almost unchanged. The hydrogenation rate was increased with the increase of either the ultrasonic frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Furthermore, a decrease in binding energy also indicated a lowered extent of metal-support interaction between the Ni phase and Si phase [2] , [74] . In this case, a shift to lower binding energies due to ultrasound has also been reported by other researchers [75] , which led to a change in electron density that may affect the bonding of chemical intermediates to the active sites, thus ultimately affecting the reaction pathways during hydrogenation [76] , [77] , [78] . Furthermore, this indication of weakening in metal-support interactions is also corroborated with the TPR studies demonstrated earlier, noting the shift in main reduction peaks to lower temperatures in sonicated samples.…”
Section: Resultssupporting
confidence: 77%
“…Furthermore, a decrease in binding energy also indicated a lowered extent of metal-support interaction between the Ni phase and Si phase [2] , [74] . In this case, a shift to lower binding energies due to ultrasound has also been reported by other researchers [75] , which led to a change in electron density that may affect the bonding of chemical intermediates to the active sites, thus ultimately affecting the reaction pathways during hydrogenation [76] , [77] , [78] . Furthermore, this indication of weakening in metal-support interactions is also corroborated with the TPR studies demonstrated earlier, noting the shift in main reduction peaks to lower temperatures in sonicated samples.…”
Section: Resultssupporting
confidence: 77%
“…[102][103][104][105][106][107] Generally, the particle size can be controlled by adjusting the ultrasonication power [96][97][98] or time. 95,96 The effect of ultrasonication on the particle size is very pronounced for the Ru-B nanoparticles. 98 The conventional Ru-B nanoparticles displayed irregular, broadly distributed particles from 15-50 nm.…”
Section: Polymer Stabilizationmentioning
confidence: 99%
“…Selectivity manipulation is generally achieved by activating the carbonyl group and/or suppressing the adsorption of the conjugated olefinic bond or the phenyl ring. 211 Ni-, 81,82,86,128 Co-, 41,80,90,96,124,[212][213][214] and Ru-based amorphous alloy catalysts 95,215,216 have been investigated in chemoselective hydrogenation of unsaturated aldehydes or ketones. In the hydrogenation of furfural (FFR) to furfuryl alcohol (FFA), Mo, Ce, and Fe are effective promoters for Ni-B or Co-B.…”
Section: 34mentioning
confidence: 99%
See 1 more Smart Citation
“…US has been used to overcome this problem and is usually reported to greatly accelerate the catalytic hydrogenation of olefins [29,54], cinnamaldehyde [55,56], 3-buten-2-ol [57,58], while selectivity to target products is either unchanged or increased under mild RT and AHP conditions. This effect has been attributed to sonication's dispersion effect on the catalyst and the effect of cavitation on the hydrogenation process.…”
Section: Ultrasonic Effects On Semi-hydrogenation Of Pa and Bydmentioning
confidence: 99%